2021
DOI: 10.3390/ijms22158155
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Salt-Stress-Responsive Genes in Barley Roots and Leaves

Abstract: Barley is characterized by a rich genetic diversity, making it an important model for studies of salinity response with great potential for crop improvement. Moreover, salt stress severely affects barley growth and development, leading to substantial yield loss. Leaf and root transcriptomes of a salt-tolerant Tunisian landrace (Boulifa) exposed to 2, 8, and 24 h salt stress were compared with pre-exposure plants to identify candidate genes and pathways underlying barley’s response. Expression of 3585 genes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Salt stress severely compromises growth and development affecting the plant survival. Gene expression is largely impacted in roots under salt stress condition (Kawasaki et al, 2001;Nefissi Ouertani et al, 2021). Nevertheless, our results showed that these synthetic promoters were not inducible in response to drought, salt, and cold stresses.…”
Section: Discussionmentioning
confidence: 49%
“…Salt stress severely compromises growth and development affecting the plant survival. Gene expression is largely impacted in roots under salt stress condition (Kawasaki et al, 2001;Nefissi Ouertani et al, 2021). Nevertheless, our results showed that these synthetic promoters were not inducible in response to drought, salt, and cold stresses.…”
Section: Discussionmentioning
confidence: 49%
“…embl.de/ipath3.cgi?map = metabolic#, accessed on 30 July 2023). 19,20 Both downregulated and upregulated DEGs were annotated using KEGG reference numbers. The visualization of metabolic pathways specifically emphasized common downregulated genes, showcasing the KEGG reference numbers associated with 20 metabolites (Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicated that the orthologous gene expression patterns were similar among DAF20, DAF40, and DAF60, while the orthologous gene expression pattern in DAF120 was different from those of samples at the other three stages in both A. latifolia and A. rufa ( Figure 1 C). Secondly, to facilitate the identification of outliers and distinguish samples with high similarity, we carried out principal component analysis (PCA) [ 25 ] according to the gene expression matrix of A. latifolia and A. rufa during different developmental periods. Our results showed that the DAF20, DAF40, and DAF60 samples from the same kiwifruit species formed a single clade, while the DAF120 samples were relatively independent ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%